Harnessing Renewable Energy for Sustainable Employment: A Comparative Study with a Focus on Iran - Sadegh Motahar (Environmental Energy and Economic Research)
The depletion of fossil fuel resources, growing environmental concerns, and efforts to mitigate climate change have led to the establishment of renewable energy technologies in various countries around the world. The social and economic benefits of renewable energy technologies include improved welfare, increased national GDP, and, notably, the creation of sustainable employment. Employment in the renewable energy industry encompasses both direct and indirect jobs, including roles in manufacturing, installation, operation, distribution, sales, and support services This paper examines job creation within the renewable energy sector across various countries and then focuses on the potential and current status of renewable energy technologies in Iran. An analysis of Iran's economic and employment landscape, along with its legislative framework for renewable energy development, reveals that despite the significant potential for job creation and export in this sector, it remains underutilized. Global investment trends highlight a particular emphasis on the photovoltaic and bioenergy sectors. Considering Iran's substantial solar energy potential and the country's electricity imbalance, coupled with the availability of university graduates, there is a strong case for advancing the renewable energy sector, especially photovoltaic technology. A comparison of employment in Iran's renewable energy sector with that of neighboring countries indicates that Iran's highest employment is in hydropower and photovoltaic sectors. However, in terms of sustainable employment in wind energy and geothermal technology, Iran significantly trails behind Turkey. The paper concludes with recommendations to maximize the job creation potential of Iran's renewable energy industry.